The Impact of Leadership Style and Compensation on Teacher Performance: A Quantitative Analysis - Rabbani, Hanif Syaifur; Rifki Suwaji (PT Mattawang Mediatama Solution, 2025)
This study examines the influence of leadership style and compensation on teacher performance at SMA Tahfidz Al Amien. The study employs a quantitative approach with a causal explanatory design. Data were collected using a structured questionnaire distributed to all 32 teachers at the school, selected through saturated sampling. Each variable was measured using multiple indicators assessed on a Likert scale. The research instrument was validated and tested for reliability, confirming that all items were valid and reliable. Data analysis was conducted using multiple linear regression with SPSS software version 16. The results show that leadership style and compensation simultaneously influence teacher performance, with a coefficient of determination (R²) of 0.507. This indicates that the two independent variables together explain 50.7% of the variance in teacher performance. The regression results also reveal that leadership style has a significant but negative effect on teacher performance, while compensation has a significant and stronger positive effect. The findings of this study suggest that compensation contributes more significantly to improving teacher performance than leadership style. These results highlight the importance of compensation as a motivational factor and point to the need for leadership approaches that better align with teacher expectations and performance goals.